Analysis Availability-Indicators of Critical Thinking Skills in Printed Physics Book - Angreini, Dea; Sari, Silvi Yulia (PILLAR OF PHYSICS EDUCATION, 2023)
Thinking skills have become the basis for implementing learning in the 21st century. Efforts that can be made to apply critical thinking skills are using teaching materials. However, no known teaching material*  includes indicators of critical thinking skills. This study the availability of critical thinking skills indicators in teaching materials. Therefore, analytical research was conducted on the availability of critical thinking skills indicators in one type of teaching material, namely printed books. This type of research is descriptive research with quantitative and qualitative approaches. The population determined in this study is the textbook for physics in high school class XI which was found in SMAN throughout the city of Padang. The research sample was physics books for class XI, which were mostly found in SMANs in Padang City. The research data was obtained by using an analysis sheet in high school physics books for class XI. Data analysis results obtained are book X with a percentage of 56.38%, book Y with 48.78%, and book Z with 56.14%. The criteria for critical thinking skills indicators in the three books are quite available.